Barriers and Priority Interventions for Public Transport Implementation in Saudi Metropolitan Cities - ElSerafi, Tamer (Journal of Construction in Developing Countries, 2026)
This study examines the principal challenges in implementing effective public transport systems in high-income Saudi metropolitan contexts, focusing on Riyadh, Jeddah and the Eastern Region. It adopts a structured decision-support approach that integrates evidence-informed item taxonomy with a modified Delphi process to validate and score implementation barriers and interventions, followed by the Best-Worst Method (BWM) weighting of decision criteria and multi-criteria decision analysis (MCDA) to generate city-specific priority rankings. The findings indicate that implementation constraints are dominated by system-level frictions rather than infrastructure alone, particularly: (1) feeder–trunk integration and transfer penalties, (2) first/last-mile walkability and safety, (3) operational reliability and service credibility and (4) access-chain thermal comfort. The cross-city results identify a “no-regret” intervention set centred on integrated fares and unified customer information, station/stop access upgrades (sidewalk continuity, safe crossings and universal accessibility) and targeted corridor operations (e.g., priority measures) complemented by a stop environment and heat-mitigation packages. Linkage mapping highlights the leverage interventions that simultaneously mitigate multiple high-priority barriers and enable actionable sequencing guidance. This study aligns recommended packages with Saudi Vision 2030/National Transport and Logistics Strategy (NTLS) objectives and Sustainable Development Goal (SDG) targets for inclusive access, safety co-benefits and climate-aligned mobility.